Ground improvement using granular pile anchor system: resistance to heave and uplift pressure - Alvin John Lim Meng Siang; Ehab Hamad Sfoog; Nahla Naji; Sim Sy Yi; Nickholas Anting Anak Guntor; Joewono Prasetijo (Institute of Advanced Engineering and Science, 2020)
Expansive soil is found in many parts of the world where its major drawback is its expansion and shrinking property upon moisture absorption and drying during alternation of rainy-dry seasons. Due to its swelling-shrinkage repeated process, fatigue and distress cause crack to structures. Granular pile anchor (GPA) system is a pioneering technique that is utilised in reinforcing these expansive soils. Granular pile anchor (GPA) system is a pioneering technique that is utilised in reinforcing expansive soils. The GPA provides tensile resistance which arrest the exerted upward forces and hence reducing heave. Previous investigations have only focused on load-displacement relationships by utilizing the pull-out technique. In this technique, an external force pulls the GPA and the corresponding displacements are recorded. The results provide indication of the GPA resistance to the applied force. However, in real conditions the heave and expansion forces were developed as a result of the pressure caused by the water absorption which pushes the entire soil bed in the upward direction along with the GPA. Therefore, this paper is aimed to explore this concept by carrying experimental and numerical investigations on a small scale model for a single pile with a diameter of 4 cm, with lengths of 20 and 40 cm. Ultimately, the reinforced soil exhibits reduction in upward force and heave compared to the unreinforced soil. Also, verifications for the testing shows that the relationship between the upward force and heave exhibits almost linear relationship for both experimental and numerical investigations. Therefore, shallow foundations incorporated with a GPA system proves to effectively lessen the heave that occurs in expansive soils which in turn can solve problems for constructions.